Students Perception of Virtual Class-Based E-Learning as a Medium for Financial Accounting Learning - Riyani, Hendri; Widiyanti, Widiyanti (Fakultas Teknik Universitas Negeri Malang, 2022)
The pandemic of COVID19 has affected education system, especially since the government issued the lockdown policy. However, it does not suspend learning ativities, which constitutes a formidable challenge for both educators and students. The purpose of this research was to know the effectiveness of the distance learning process through the use of Google Classroom in financial accounting class at Public Vocational High School 1 of Pagerwojo, Tulungagung. This was quantitative research using descriptive method and focusing on the evaluation of the learning process through online media. The research population was the eleventh-grade students, majoring in Accountung and Financial Institutions (AFI). The research involved 32 of AFI 1 students as the research sample. The reserach data were colleted using questionnaires, and the data were analyed using descriptive statistics. The research found that the distance learning using Google Classroom is effective enough. This is corroborated by the fact that students prefer Google Classroom to other online media, because they feel that the features of Google Classroom are easy to understand and run.